Perfil hemostático de cães portadores de neoplasia mamária maligna - Mariah Gois Ceregatti (2022)
Mammary neoplasms in dogs are extremely important in veterinary oncology due to its high incidence, histological diversity or as a result of paraneoplastic syndromes. The presence of hemostatic dyscrasias has been well described in humans and is correlated with a worse prognosis. Inflammatory mammary carcinoma (IMC) is a locally invasive, extremely aggressive clinical-pathological presentation with a high metastatic potential, an acute course and an unfavorable prognosis. The aim of this study was to determine the hemostatic profile in dogs with IMC and to compare it to that of patients with non-inflammatory mammary carcinomas and to a group of healthy patients. Fifty- eight dogs divided into four groups participated in this study: healthy patients (CONTROL, n=25); inflammatory mammary carcinoma (IMC, n=9), mammary neoplasia without metastasis (NMSM, n=12) mammary neoplasia with metastasis (NMCM, n=12). A complete physical examination was performed, with special attention to the examination of the mammary glands, clinical staging by the TNM system, blood count, hemostatic evaluation, consisting of platelet concentration, prothrombin time (PT), activated partial thromboplastin time (PTT), fibrinogen concentration, d-dimer concentration; and the histopathological examination were performed. The platelet concentration differed from the CONTROL only for the NMCM group, which presented the highest concentrations, whereas the CIM and NMSM groups were equivalent to each other and to the CONTROL. The PT of the IMC group was shortened when compared to the CONTROL and the fibrinogen concentrations and d-dimers were greater, however such parameters were statistically equivalent to the NMSM and NMCM groups. For PTT, in the CIM and NMCM groups there was a prolongation when compared to the CONTROL, the NMSM group was equivalent to the other groups. The results obtained in this study suggest that mammary neoplasia induce hemostatic changes, probably due to inflammation, especially in patients with inflammatory carcinoma.